From waste to energy: A systematic review of sewage sludge conversion to solid fuels via thermochemical methods - Roslan, Siti Zaharah; Idris, Juferi; Musa, Mohibah; Md Zaini, Mohd Saufi; Anuar, Nur Faradila; Iskandar Shah, Darween Rozehan Shah; Mohd Tahir, Muhamad Iqbal Hakim (Center of Biomass & Renewable Energy (CBIORE), 2025)
Sewage sludge, a byproduct of wastewater treatment, poses significant risks to human health and ecosystems due to its high levels of harmful pollutants, including heavy metals, viruses, and non-biodegradable materials. To mitigate these hazards, thermochemical conversion has emerged as a sustainable strategy for recovering energy and nutrients while reducing the toxicity of sewage sludge. A comprehensive literature search across Science Direct, Scopus, and Web of Science yielded 46 peer-reviewed papers from an initial 2,715 publications. This paper presents a systematic review of the thermochemical conversion processes used to transform sewage sludge into solid fuels, focusing on pyrolysis, torrefaction, and hydrothermal carbonization. The study highlights the significance of optimizing operational parameters and investigates the physicochemical properties of the biochar produced. The results indicate that reaction temperature, time, and heating rate significantly influence the quality and yield of the resulting biochar. Higher temperatures (300–1000°C) enhance the energy content while reducing solid yield. The environmental impacts associated with thermochemical methods, including emissions and potential pollutants, are discussed along with the challenges in treating and transforming sewage sludge into solid fuels. These findings indicate that hydrothermal carbonization is a promising method for waste management and energy production, supporting global efforts to reduce greenhouse gas emissions and dependence on fossil fuels. However, challenges remain in scaling up these technologies for commercial implementation due to high capital and operational costs This review contributes to the understanding of thermochemical processes and their potential applications in sustainable waste-management practices. Future research should focus on pilot and industrial-scale validation, cost-effective pretreatment strategies, and standardized analytical methods. Supportive policy frameworks and investment in demonstration projects are crucial for promoting thermochemical conversion as a viable waste-to-energy solution, contributing to sustainable development and climate change mitigation.